2004
DOI: 10.1128/jcm.42.6.2508-2517.2004
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Diversity of the cag Pathogenicity Island among Helicobacter pylori Strains in Japan

Abstract: The severity of Helicobacter pylori-related disease is correlated with the presence of a cag pathogenicity island (PAI). Genetic diversity within the cag PAI may have a modifying effect on the pathogenic potential of the infecting strain. We analyzed the complete cag PAI sequences of 11 representative Japanese strains according to their vacA genotypes and clinical effects and examined the relationship between the diversity of the cag PAI and clinical features. The cag PAI genes were divided into two major grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 32 publications
1
68
0
Order By: Relevance
“…A region of approximately 1 kb in the cag pathogenicity island that includes cagQ was reported to be inverted in some Japanese strains (15). Our detailed sequence comparison confirmed a similar inversion in Shi470 and in three out of the four Japanese genomes and, furthermore, strongly suggested that these inversion events likely occurred by two steps of DDAI with generation of inverted repeat pairs of 87 bp and 82 bp (Fig.…”
Section: Linkage Of Changes In Number Ofsupporting
confidence: 63%
“…A region of approximately 1 kb in the cag pathogenicity island that includes cagQ was reported to be inverted in some Japanese strains (15). Our detailed sequence comparison confirmed a similar inversion in Shi470 and in three out of the four Japanese genomes and, furthermore, strongly suggested that these inversion events likely occurred by two steps of DDAI with generation of inverted repeat pairs of 87 bp and 82 bp (Fig.…”
Section: Linkage Of Changes In Number Ofsupporting
confidence: 63%
“…In contrast, there is no significant correlation between the vacA genotypes and gastroduodenal disease in East Asian countries. The results of several studies have indicated that some Asian strains are influenced by genetic exchange with neighboring countries and are similar to other isolates from Western countries (Yamaoka et al, 2002;Azuma et al, 2004;Yamazaki et al, 2005;Satomi et al, 2006;Latifi-Navid et al, 2010), Whereas none of the Western strains have an East-Asian-type gene sequence (Xia et al, 2009). Since East Azerbaijan, like Ardabil and Mazanderan could be considered as the high incidence areas of GC in Iran (Somi et al, 2008;Latifi-Navid et al, 2013), H pylori strains from this region also might be similar to other isolates from Western Eurasia and placed in the hpEurope population (Latifi-Navid et al, 2010).…”
Section: Discussionmentioning
confidence: 90%
“…We hypothesize that the absence and relatively low percentage of H. pylori isolates carrying the more carcinogenic D or multiple C EPIYA motifs could be the main factor that influences the low rate of GC in our country. The absence of East-Asian CagA type in our study was an expected result, since this type is almost restricted to East Asian patients (38)(39)(40)(41). EPIYA-D motif represents the CagA genotype with the highest association to premalignant lesions and GC development in infected persons (15,16).…”
Section: Hpcnic-74 Nfsdikkelnakl-gnfnnnnnnglkn-------epiyakvnkkkagqaamentioning
confidence: 82%